Isu-isu profesionalisme dalam Perlembagaan Persekutuan Malaysia - Nazri Muslim, (Universiti Kebangsaan Malaysia, 2011)
For a sovereign state, the constitution is seen as the source of the supreme law of the country in which each individual must behold. Its existence is as a guide for organizing and coordinating the government of a country. In addition, the Constitution also serves as a guide for the establishment of law whether in the government or citizens or anyone else. This is because the Constitution expressly provides in Article 4(1) that the constitution is the primary federal law and all laws passed after the independence as well as laws that are contrary to the constitution must be void to the extent of the contrary. Compliance with the provisions of the constitution will lead to build professionalism among the people as this refers to its role to build upon one’s ability and responsibility towards the given trusts. This paper highlights issues on professionalism in the constitution with reference to Article 3, Article 8, Article 11 and Article 153 and other relevant provisions.